From generic to organic competencies - Joseph A. Raelin; A. Sims Cooledge (Human Resource Planning, 1995)
A study was performed to determine whether an "organic" set of competencies might be beneficially derived for a specific managerial population based upon the use of a prior "generic" competency instrument. The organic set differed substantially but was found to be useful as an indicator of performance of the day-to-day operating duties of the managers. The data from the organic instrument were found to be particularly valuable as a thermometer of developmental needs. The study suggests that generic competency instruments might not be consistently interpreted by local users nor commensurate with workplace dimensions. Thus, deployment of off-the-shelf instruments may prove unreliable and invalid without situational customization.
Keywords: M10; M12; M14; M50; M51; M53; 650; Competencies; Organic competencies; Human resource planning; Human resource development; Performance evaluation; Leadership development